PHYSICO-CHEMICAL PARAMETERS AND HPTLC FINGERPRINTING PROFILE OF DILLENIA INDICA MIQ. F. ELONGATA (MIQ.) AND TECTONA GRANDIS LINN. WITH REFERENCE TO BETULIN - PREET AMOL SINGH; VIDHU AERI (International Journal of Pharma and Bio Sciences, 2016)
The present study was carried out to evaluate physicochemical parameters and HPTLC fingerprinting profile of Dillenia indica Miq. f. elongata (Miq.) and Tectona grandis Linn. with reference to betulin. Physicochemical parameters such as ash value (total ash, acid insoluble ash), loss on drying, alcohol soluble extractive, water soluble extractive were evaluated using WHO guidelines. HPTLC fingerprinting profiling was performed using Camag Linomat applicator model V, Camag TLC visualizer. Samples were applied on aluminium HPTLC silica gel plates 60 F254 p. Solvent system i.e. n-Hexane-Ethyl Acetate (8:2) was developed for betulin separation. Camag TLC developing chamber was used for developing the profile of given samples. Finally developed TLCs were derivatized in chromatogram immersion device III with anisaldehyde sulphuric acid reagent. The physicochemical parameters of the plants were found to be in proper range as per WHO guidelines and available literature. The violet and fluorescent golden band of betulin was observed in white light and at 366nm respectively after derivatization with anisaldehyde sulphuric acid reagent. Physico-chemical properties can provide valuable information regarding plant identification and its authentication. Betulin, a known pentacyclic triterpenoid is known to exhibit diverse pharmacological properties. Hence, the stem barks of Dillenia indica Miq. f. elongata (Miq.) and Tectona grandis Linn. can be effectively utilized for the isolation of betulin.